(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
In the Uzbek Cyrillic alphabet, the letter Ee represents the combination of the sound [э] ([e]) and [й+э] ([y+e]). In the Uzbek Latin alphabet, it is used only in place of the phoneme [э] ([e]). This causes a number of complications in the transliteration of words with this letter into the Uzbek Latin alphabet. For this reason, a scientific-theoretical approach, comparative analysis and practical experience are necessary to translate words with the letter Ee into Latin.